An Experimental Study on the Relationship Between Temperature and Pressure Inside the Cup During Cupping Procedures - Ha Lim Lee; Soo Kwang An; Jae Yong Lee; Dong Wook Shim; Byung Ryul Lee; Gi Young Yang (MEDrang Inc., 2021)
Background Pressure changes related to temperature variation during cupping may lead to dropout. This study aimed to investigate pressure changes related to temperature variations in the cup during the cupping procedure. Methods Changes in temperature and pressure were measured for 15 minutes after the procedure was performed using the alcohol rub method with glass cups and with the addition of infrared irradiation. Changes in temperature and pressure were also measured for 15 minutes after pumping 3 times using the valve suction method, and with the addition of infrared irradiation. Results In a comparison between the alcohol rub method with glass cups and with the addition of infrared irradiation, the negative pressure increased over time in the absence of infrared irradiation, whereas it decreased when performed with infrared irradiation p = 0.094. However, in a comparison between pumping 3 times using the valve suction method, and with the addition of infrared irradiation, the negative pressure decreased in both cases, but this was more significant with infrared irradiation p = 0.172. There was a significantly higher temperature in the glass cups (p = 0.004) and the valve cups (p = 0.001) exposed to infrared radiation, compared with no infrared irradiation. Conclusion The reduction in negative pressure inside the cups exposed to infrared radiation was greater than without infrared irradiation. Temperature increases inside the cup can lead to the risk of dropout.